Radiation exposure during chest X-ray examinations in a premature intensive care unit: phantom studies - Dütting, Tanja; Foerste, Birgit; Knoch, Thilo; Kassa Darge; Tröger, Jochen (Pediatric radiology, 1999)
There are few reports on the radiation dose received by infants, their family and radiographers exposed to scatter radiation in a premature baby intensive care unit. To evaluate the degree of radiation exposure from diagnostic X-ray examinations with mobile X-ray machines in a premature intensive care unit.